Enhanced humoral response in pregnant mice immunized with liposome encapsulated recombinant neutralizing epitope protein of Hepatitis- E virus - Joshi, Shivali Shirish (Virol J, 2015)
BACKGROUND: Pregnant women from developing countries are at high-risk of hepatitis E-associated high mortality and constitute priority population for vaccination. So far, candidate vaccines have not been evaluated during pregnancy. We evaluated our vaccine candidate, recombinant Neutralizing Epitope protein (rNEp) encapsulated in liposomes, in pregnant mice. METHODS: A single dose (10 μg) of the formulation was administered intramuscularly on day 7 of pregnancy. Titres of serum IgG antibodies to hepatitis E virus (IgG-anti-HEV), levels of cytokines and biochemical parameters were determined. Spleens were harvested from pregnant and non-pregnant mice for immunophenotyping (flow cytometry), cytokines (cytometric bead array, CBA) and gene expression of immune response genes (Taqman low density array, TLDA). Histopathology studies of spleen, liver, kidneys, brain and muscle was carried out. RESULTS: The vaccine was well-tolerated during pregnancy as evidenced by histopathology and serum biochemical parameters. Anti-HEV titres were significantly higher in the pregnant balb/c and C57BL/6 mice (3592 ± 802 and1016 ± 138 respectively, than in non-pregnant groups (634 ± 191 and 320 ± 55 respectively, p < 0.001 for both) suggesting that the higher antibody response in pregnant mice was independent of the genetic makeup of the host but immunogen-driven. Pups receiving vertically transferred antibodies developed lower anti-HEV antibodies (p < 0.05) when immunized with the formulation after seronegativity than in the age-matched mice without such antibodies. In non-pregnant mice, a Th1 response and discordance between splenic and serum cytokines was evident while in pregnancy, a Th2 bias was observed irrespective of immunization. Increased CD19 levels correlated with higher anti-HEV titres in pregnant mice. CONCLUSION: The single dose of the vaccine was safe and highly immunogenic in pregnant mice. Degree and type of immune response to vaccination during pregnancy is immunogen-driven. In-depth studies are needed to understand the underlying immunologic mechanism(s). These encouraging results for a vaccine intended for use in pregnant women should be confirmed in higher animals.